(untitled) - Nhan, Minh Trí (Australia, 2013)
This thesis showed that environment mainly influenced grain quality; both genotype and environment affected strongly starch granule characteristics; and all of genotype, environment and processing influenced significantly starch functional properties, including in vitro enzymatic digestibility.
Keywords: Lúa mì